The memory collector [compact disc, unabridged] - Gardiner, Meg (Brilliance Audio, 2009)
Forensic psychiatrist Jo Beckett is called to the scene of an aircraft inbound from London to help deal with a passenger who is behaving erratically. She figures out that he's got anterograde amnesia, and can't form new memories. Suddenly a string of clues arises, something to do with a super deadly biological agent code-named "Slick," a missing wife and son, and a secret partnership gone horribly wrong. Jo realizes her patient's addled mind may hold the key to preventing something terrible from happening in her beloved San Francisco. In order to prevent it, she will have to get deeper into the life of a patient than she ever has before, hoping the truth emerges from the fog of his mind in time to save her city--and herself.